Pengaruh Pendekatan Latihan Massed Practice Terhadap Keterampilan Renang Gaya Dada Mahasiswa Prodi Pendidikan Olahraga dan Kesehatan Angkatan 2014 - Ilham Ilham; Alek Oktadinata; Meri Haryani (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of Massed Practice practice approaches to chest-breast style skills. The research is an experimental research, which in this research there is treatment that is the application of Massed Practice approach. to determine the effect of something imposed on the sample to be studied. This experimental study was conducted in the Sports and Health Education Study Program with a total of 28 samples. Sampling in this research using clustering technique or sampling sampling area. The data obtained through the observation sheet of chest pool skills.The collected data were analyzed by using t test but previously tested normality and homogeneity. The conclusion of this research is that there is significant influence of Massed Practice practice approach to chest pool skill in student of Prodi Porkes class of 2014.